Two new marine hermit crabs allied with the Paguristes tortugae complex (Crustacea: Decapoda: Anomura) from the western Atlantic - Craig, Catherine W.; Felder, Darryl L. (Zootaxa, 2022)
A recent molecular phylogenetic analysis that focused on selected species of western Atlantic Paguristes Dana, 1851, Areopaguristes Rahayu & McLaughlin, 2010, and Pseudopaguristes McLaughlin, 2002 was somewhat inconclusive regarding relationships among those genera, but it revealed two new unrecognized species genetically related to members of the Paguristes tortugae complex. One of the new species is sister to A. hummi (Wass, 1955), which is readily separated from Wass’ taxon by significant differences in coloration. However, no definitive characters have been found for its identification on the basis of structural morphology. A second new species is genetically sister to P. tortugae Schmitt, 1933, even though it was regarded in earlier literature as no more than an ecomorphic variant expressing protective coloration related to habitat substrate color. In addition to its unique coloration, subtle distinctions are evident in structural morphology. Both species are formally named with accompanying morphological and color descriptions.